Institutional Environment of Innovation Market: Structure and Factors of Development - Prokin, Valeriy V.; Lepikhina, Ð¢atyana L.; Anisimova, Ekaterina L.; Karpovich, Yuliya V. (International Journal of Economics and Financial Issues, 2015)
The article is devoted to the research of theoretical approaches to the analysis of institutional factors in the development of innovations. A structural factor model of innovation systems is presented in the article. The key object of factor analysis in the model as well as is the definition of institutional factors of innovation environment is determined. Institutional environment of innovative market is structured. Endogenous and exogenous factors that influence the development of the institutional environment, barriers hindering the development of the innovative environment are identified. Keywords: institutional environment, innovative system, institutional factors, institutions, barriers JEL Classifications: O33; O38; R11